Prototipe Sistem Informasi Monitoring Kebakaran Bangunan Berbasis Google Maps dan Modul GSM - Sri Safrina Dewi; Dedi Satria; Elin Yusibani; Didik Sugiyanto (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2017)
The fire disaster was one of the disasters that frequently occurred in Indonesia. Fires often occur in particular in the area of dense population average is affected by the presence of shorting electric and gas leakage from household kitchens. many cases fires are known at the time of the fire, and little has happened can be detected early. Based on community-based information system that has been done today, then needed a fire disaster information systems that can provide information and notification in real-time in the form of initial conditions information from source fire and its location to the firefighter or the community effectively and efficiently. The purpose of the research was the design of a prototype fire information system building based Google Map using lines of communication the GSM module. The prototype was built using the DHT11 temperature sensor, Sensor Smoke MQ2, Arduino Uno, GPS module and GSM modem SIM9000. The research produces information systems monitoring fires in two systems namely fire detection system and information systems fire location based Google Maps. Both systems have been run in accordance with experiments that have been conducted resulting in fire occurrence data location information with data on the condition of the presence of smoke and temperature/temperature. And expected with this prototype development research community or parties associated with catastrophic fires can be helped to anticipate disasters and takes a lot of sacrifice.